"I don't know if I can talk about that": An Exploratory Study on the Experiences of Care Workers Regarding the Sexuality of People with Intellectual Disabilities - Alan Santinele Martino; Jordyn Perreault-Laird (Disability Studies Quarterly, 2019)
This exploratory study examined the attitudes and experiences of a small sample of direct care workers' experiences of addressing the sexual expression and practices of their clients with intellectual disabilities. Drawing on in-depth interviews with direct care workers in Alberta, Canada, we use Foucault's work to examine the way power is exercised through organizational policies, personal values, and employment contexts. Altogether, the accounts of direct care workers seem to illuminate a culture that commonly sees disability and sexuality as antithetical and a topic to be avoided for fear of reprisal.
Keywords: intellectual disability; sexuality; front-line support work; qualitative interviews; Alberta; Canada